An Energy Saving House from 3400 Years Ago - Irene Staeves (EXARC, 2016)
New conclusions concerning the supporting construction. The fact that people of the Bronze Age built houses with very good insulation was already presented by Staeves (2010) based on the results of an archaeological excavation in 2003 where an archaeological team of the Main-Kinzig district examined remnants of a Middle Bronze Age settlement. Prior to this, it was assumed that the walls of Bronze Age houses consisted of one wattle that was covered with clay on either side. The burnt fragments of clay found in Langenselbold (2003) show that here the walls consisted of two parallel wattles with the space in between being filled with dry grass. Pieces of clay were recently analysed that let us conclude how the wattles were fixed in the upholding construction. This will be described in the next five chapters. In the following section, a review will be given concerning the findings that explain the two wattle constructions.